Ocular inflammatory disease and ocular tuberculosis in a cohort of patients co-infected with HIV and multidrug-resistant tuberculosis in Mumbai, India: a cross-sectional study - Mehta, Salil (BioMed Central, 2013)
BACKGROUND: The prevalence and the patterns of ocular inflammatory disease and ocular tuberculosis (TB) are largely undocumented among Multidrug Resistant TB (MDR-TB) patients co-infected with Human Immunodeficiency Virus (HIV) and on antituberculosis and antiretroviral therapy (ART). METHODS: Lilavati Hospital and Research Center and Médecins Sans Frontières (MSF) organized a cross-sectional ophthalmological evaluation of HIV/MDR-TB co-infected patients followed in an MSF-run HIV-clinic in Mumbai, India, which included measuring visual acuity, and slit lamp and dilated fundus examinations. RESULTS: Between February and April 2012, 47 HIV/MDR-TB co-infected patients (including three patients with extensively drug-resistant TB) were evaluated. Sixty-four per cent were male, mean age was 39 years (standard deviation: 8.7) and their median (IQR) CD4 count at the time of evaluation was 264 cells/μL (158–361). Thirteen patients (27%) had detectable levels of HIV viremia (>20 copies/ml). Overall, examination of the anterior segments was normal in 45/47 patients (96%). A dilated fundus examination revealed active ocular inflammatory disease in seven eyes of seven patients (15.5%, 95% Confidence Intervals (CI); 5.1-25.8%). ‘These included five eyes of five patients (10%) with choroidal tubercles, one eye of one patient (2%) with presumed tubercular chorioretinitis and one eye of one patient (2%) with evidence of presumed active CMV retinitis. Presumed ocular tuberculosis was thus seen in a total of six patients (12.7%, 95% CI; 3.2-22.2%). Two patients who had completed anti-TB treatment had active ocular inflammatory disease, in the form of choroidal tubercles (two eyes of two patients). Inactive scars were seen in three eyes of three patients (6%). Patients with extrapulmonary TB and patients <39 years old were at significantly higher risk of having ocular TB [Risk Ratio: 13.65 (95% CI: 2.4-78.5) and 6.38 (95% CI: 1.05-38.8) respectively]. CONCLUSIONS: Ocular inflammatory disease, mainly ocular tuberculosis, was common in a cohort of HIV/MDR-TB co-infected patients in Mumbai, India. Ophthalmological examination should be routinely considered in HIV patients diagnosed with or suspected to have MDR-TB, especially in those with extrapulmonary TB.